Polygonum multiflorum Thunb.: A Review on Chemical Analysis, Processing Mechanism, Quality Evaluation, and Hepatotoxicity - Liu, Yue; Wang, Qi; Yang, Jianbo; Guo, Xiaohan; Liu, Wenxi; Ma, Shuangcheng; Li, Shaoping (Frontiers in Pharmacology, 2018)
Abstract: Polygonum multiflorum Thunb. and its processed products have been used in China for centuries due to their multiple beneficial effects to human body. Currently, liver injuries caused by taking P. multiflorum have been reported worldwide, but the potential toxic components and possible mechanism that caused hepatotoxicity remain unclear. It is worth noting that the processing procedure could significantly decrease the toxicity of raw P. multiflorum and the processed products of P. multiflorum are considered to be relatively safe. However, the processing mechanism is still ambiguous, and there is the lack of a scientific approach to control the quality of P. multiflorum praeparata. This study is the first review that summarizes the recently advances (from 2007 to 2017) in the chemical analysis of P. multiflorum, and provides comprehensive information on the quantitative and qualitative analysis of P. multiflorum as well as its related species. In addition, the processing mechanism and quality evaluation of processed P. multiflorum are discussed. Moreover, the toxicity of P. multiflorum is analyzed from the perspectives of exploration of the proposed toxic ingredients, metabolite identification, metabolomics studies and exogenous contaminant determination. Furthermore, trends and perspectives for future research of this medicine are discussed.